2011
DOI: 10.1097/hcm.0b013e3182078ba4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Perceived Threat of Malpractice Lawsuits by Various Medical Specialists

Abstract: A study was undertaken to examine perceived threat of malpractice lawsuits affecting different physician specialties and to examine factors that impact such perceptions of those specialties. The study used data collected by the Center for Studying Health System Change's 2008 Health Tracking Physician (HTP) Survey. The 2008 HTP data set consisted of 4720 physicians belonging to the American Medical Association. Primary care physicians, medical specialists, surgical specialists, psychiatrists, and obstetricians/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Yet payments for claims judged in court still accounted for less than a fifth of the total payment amount in 2009. Again, these findings may contribute to perceptions that medical malpractice claims lead to exorbitant payouts driven by out-of-control juries, even though the number of judged claims is low,9 21 equating to about 0.0003 claims per practicing physician.…”
Section: Discussionmentioning
confidence: 95%
“…Yet payments for claims judged in court still accounted for less than a fifth of the total payment amount in 2009. Again, these findings may contribute to perceptions that medical malpractice claims lead to exorbitant payouts driven by out-of-control juries, even though the number of judged claims is low,9 21 equating to about 0.0003 claims per practicing physician.…”
Section: Discussionmentioning
confidence: 95%
“…The results of this study are consistent with the findings of studies conducted in Turkey (54), Taiwan (55), Germany (56), United Kingdom (57), USA (58), and Saudi Arabia (59), in which gynaecologists had the highest number of complaints. The surgical team is always the main target of medical complaints due to the invasive nature of their medical practices (60). In a study in Spain, most complaints have been reported against gynaecologists, orthopaedist, neurosurgeons, ophthalmologists, and anaesthesiologists (61).…”
mentioning
confidence: 99%
“…20 Factors that can improve career success of female medical school faculty include a flexible work environment, departmental mentoring, and staff support for grant and manuscript preparation. [25][26][27][28] As such, this clearly implies that the average male physician may benefit greatly by working on their ''soft'' skills. This is consistent with previous research that found that medical malpractice claims were much higher among male physicians.…”
Section: Discussionmentioning
confidence: 99%